ANALYSIS OF DIGITAL POPULATION IDENTITY SERVICES IN BANDUNG CITY - Gatiningsih Gatiningsih; Aris Prihandono; Dewi Kurniasih; Sri Rum Giyarsih (Jurnal Ilmiah Wahana Bhakti Praja, 2025)
The Digital Population Identity (DPI) activation program aims to enhance efficiency and ease of access to public service data. Bandung City, as one of the municipalities implementing the DPI program, possesses relatively advanced digital infrastructure; however, the DPI activation rate remains low at 3.8%, far below the national target of 30%. This study aims to examine the implementation of DPI services, identify supporting and inhibiting factors affecting DPI achievement, and formulate strategies for improvement. The research adopts a descriptive qualitative approach, with data collected through in-depth interviews, observation, and document analysis. Research informants include heads of local government agencies, service implementation officers, and members of the public as service users. Data analysis was conducted through data reduction, data display, and conclusion drawing. The analytical framework is based on Zeithaml’s public service quality theory, which comprises five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The findings indicate that the Tangibles dimension, particularly application availability and supporting facilities, is generally adequate. However, significant constraints are identified in the Reliability dimension due to central network disruptions and limitations of users’ devices. The Responsiveness dimension, implemented through proactive outreach strategies (“jemput bola”) and mobile services (“Mepeling”), has proven to be a key success factor in areas with the highest activation rates, such as Astana Anyar District (7.8%). Spatial data visualization analysis confirms disparities in activation achievement across districts, influenced by variations in digital literacy levels and public trust in data security (Assurance). The recommended strategies for improvement include strengthening the reliability of technical systems and optimizing proactive, area-based services to accelerate progress toward the national DPI activation target. Keywords: Activation achievement, service quality, responsiveness, digital literacy, data security, system reliability, proactive services.